Evidence for intra-mitochondrial variation in population genetic structure of Platycephalus sp.1 In the Northwestern Pacific. (17th February 2019) - Xu, Shengyong; Wang, Zhiyang; Zhang, Yan; Gao, Tianxiang; Zou, Jianwei; Zhang, Xiumei
Abstract: Understanding evolutionary dynamics of population structure and genetic diversity of marine fish species is of great importance for fishery management and resource conservation. Platycephalus sp.1 is a commercially important marine fish in the Northwestern Pacific. Yet, current understanding of population genetic patterns of Platycephalus sp.1 remains limited. In this study, the Platycephalus sp.1 individuals from four populations in the Northwestern Pacific, which cover large geographic distances and latitudinal gradients, were sampled to examine genetic diversity and population structure by investigating the mitochondrial sequences of Cytochrome b (CYTB, 1141 bp) and control region (CR, 458 bp), and then to assess intra-mitochondrial genetic variability by using a combination of population- and individual-based analytical approaches. Moderate to low levels of genetic diversity were observed in sampled populations by investigating both CR and CYTB datasets. In CR dataset, weak genetic differentiation among populations were observed and population Tokyo Bay was significantly differentiated with other sampled populations. In CYTB dataset, lower genetic differentiations were observed and population Beihai (BH) was significantly differentiated. A non-synonymous substitution was predominantly detected in population BH, and such substitution was tested as a significantly positive selective site in natural selection tests. Based on these findings, we propose that local adaptation influenced by natural selection contributes largely to the intra-mitochondrial variation in Platycephalus sp.1 populations. The present study provides new perspectives on the population genetic structure of Platycephalus sp.1, which could have important implications for the sound management and conservation of this fishery species.